2014
DOI: 10.1111/echo.12823
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Appendage Flow Velocity and Time from P‐Wave Onset to Tissue Doppler–Derived A' Predict Atrial Fibrillation Recurrence after Radiofrequency Catheter Ablation

Abstract: LAAFV (reflecting functional remodeling) and PA-TDI (reflecting electrical remodeling) are independent predictors of AF recurrence after RFCA for PAF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 39 publications
0
32
1
Order By: Relevance
“…The prolonged value of 146 ± 20 ms was associated with AF recurrence after CA (for comparison PA-TDI in healthy subjects was 78 ± 7 ms) [42]. Similarly, Fukushima et al [43] found that PA-TDI was an independent predictor of AF recurrence in patients with paroxysmal AF. They reported 2.…”
Section: Left Atrial Mechanical Dyssynchronymentioning
confidence: 94%
“…The prolonged value of 146 ± 20 ms was associated with AF recurrence after CA (for comparison PA-TDI in healthy subjects was 78 ± 7 ms) [42]. Similarly, Fukushima et al [43] found that PA-TDI was an independent predictor of AF recurrence in patients with paroxysmal AF. They reported 2.…”
Section: Left Atrial Mechanical Dyssynchronymentioning
confidence: 94%
“…In clinics, echocardiography is widely used to measure LAA volume and functions. LAA structure and function may provide predictive value for PAF recurrence after RFCA . Transthoracic echocardiography (TTE) image is inferior to TEE, because TEE allows rotation of heart structures and enables accurate visualization of the cardiac chambers by slicing the images in any plane.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive TTE study that included M‐mode, two‐dimensional, continuous‐wave, pulsed‐wave, and color flow Doppler echocardiography was performed, as described previously . Aortic root diameter at the sinus of Valsalva was measured according to the current convention at end‐diastole in the parasternal long‐axis view that showed the maximum diameter parallel to the aortic annular plane .…”
Section: Methodsmentioning
confidence: 99%
“…A comprehensive TTE study that included M-mode, two-dimensional, continuous-wave, pulsed-wave, and color flow Doppler echocardiography was performed, as described previously. 15 Aortic root diameter at the sinus of Valsalva was measured according to the current convention at end-diastole in the parasternal long-axis view that showed the maximum diameter parallel to the aortic annular plane. [16][17][18] Vivid E9 (GE Healthcare, Horten, Norway), an Artida (Toshiba Medical Systems, Tokyo, Japan), SONOS 4500/5500 (Philips Healthcare, Bothell, WA, USA), or iE33 (Philips Healthcare) ultrasound machines were used for TTE examinations.…”
Section: Echocardiographymentioning
confidence: 99%